Cours interactif et performance académique d'étudiants de première année universitaire en économie - Alain de Crombrugghe; Marc Romainville
The paper studies the added value of an interactive learning method with regular monitoring compared to a classical teaching method combining lectures and exercises for a first-year economics course at the University of Namur (Belgium). The evaluation is based on an independent evaluation of the initial skills of the students and on their final results in economics and across all subjects for their first year. It examines both differences in grades between students in the experimental group and those of the control group, and the distribution of these differences across the students in both groups. The analysis assumes that there is no hidden variable that characterizes the students belonging to the interactive group that cannot be captured by the initial measurement of skills. Therefore, the data suggest that the interactive method, including its monitoring of students and dialogues with the teacher, has an added value for the academic performance of students due to their motivation and engagement. Nonetheless, it does not enable all students to achieve a pass grade and it displays its strongest effects at both ends of the distribution of initial skills. Students' oral comments underline the benefits of regular work, cooperation with other students, discussions with the teacher and progressive understanding of the required quality of work.